THE IMPORTANCE OF TOURISM INFORMATION AND PROMOTION OFFICE AND CENTRES IN THE DEVELOPMENT OF INBOUND TOURISM - Nicolae PLATON (Economica, 2017)
Development of individual economies of countries of the world, reducing trade barriers and broadening international economic and cultural exchanges, as well as globalization have created favorable conditions for the participation of a growing number of countries and people in tourism traffic. Pretenders to be included in the tourism circuit should provide: individualization of supply,therefore, are focused on the type of holiday they want to spend. Thus, countries with tourism potential that intend to attract foreign tourists need to know who they are, from which country, age, interests, in order to meet their requirements and requests. In this context, it is argued the role and need for the creation of Office and Tourism Information and Promotion Centers in attracting and qualitative service of foreign tourists.